Comparative efficacy of two medicinal plants and Amaryl® tablet (Glimepiride) in induced diabetes mellitus in rat (Journal of the Bangladesh Agricultural University, 2010)
Comparative efficacy of two indigenous herbal extracts, (Trigonella foenum-graecum seed & Coccinia indica leaves) with the commonly used drug Glimepiride were studied. Healthy young rats (n=30) of both sexes weighting between 150 to 200 gm were selected and divided into six equal groups, as A (Control), B (diabetic), experimental diabetic groups were-C, D, E and F, treated with combined extract of Methi seed and Telakucha leaves- @ 250mg, 500mg, 750mg and Glimepiride 800μg/kg body weight, respectively. The substances were given orally once daily for14 days. The blood glucose concentration were decreased significantly (P